Prescribing-Assessment Tools for Long-Term Care Pharmacy Practice: Reaching Consensus through a Modified RAND/UCLA Appropriateness Method - João R. Gonçalves; Betsy L. Sleath; Manuel J. Lopes; Afonso M. Cavaco (Pharmacy, 2021)
Medicines are the most used health technology in Long-Term Care. The prevalence of potentially inappropriate medicines amongst Long-Term Care patients is high. Pharmacists, assisted by prescribing-assessment tools, can play an important role in optimizing medication use at this level of care. Through a modified RAND/UCLA Appropriateness Method, 13 long-term care and hospital pharmacists assessed as ‘appropriate’, ‘uncertain’, or ‘inappropriate’ a collection of commonly used prescribing-assessment tools as to its suitability in assisting pharmacy practice in institutional long-term care settings. A qualitative analysis of written or transcribed comments of participants was pursued to identify relevant characteristics of prescribing-assessment tools and potential hinders in their use. From 24 different tools, pharmacists classified 9 as ‘appropriate’ for pharmacy practice targeted to long-term care patients, while 3 were classified as ‘inappropriate’. The tools feature most appreciated by study participants was the indication of alternatives to potentially inappropriate medication. Lack of time and/or pharmacists and limited access to clinical information seems to be the most relevant hinders for prescribing-assessment tools used in daily practice.